Influence of Motivational Practices on Teachers’ Performance in Secondary Schools Kamwenge District. - Prudence, Hanga (Kabale University, 2020)
The study was about “Influence of Motivational Practices on Teachers’ Performance in secondary Schools in Kamwenge District”. It had the following objectives; to examine the types of motivational practices in Secondary Schools in Kamwenge District, to assess the level of teachers’ performance in Secondary Schools in Kamwenge District, to establish the relationship between the types of motivational practices and teachers’ performance in Secondary Schools in Kamwenge District. The study was qualitative and quantitative; used cross section design which was descriptive in nature. The study used purposive, stratified, and simple random sampling retinues to select the research respondents respectively from secondary schools. The target population was 200 and the sample size of respondents was 133. Data was collected using questionnaires, interview documentation analysis and observation as the research instruments and data was analyzed by means of descriptive statistics, namely frequencies, percentage and mean. Pearson correlation coefficient was used to establish the relationship between motivational practices and teachers’ performance in secondary schools. The study findings that people enjoying teaching as a profession was strongly agreed to by the majority of the respondents with 65% while free meals at school was in the lead on extrinsic motivation with 83.6%. Regular attendance of class lessons by teachers was rated at 83.3%, and performance of teachers being good and encouraging at 77%.The study found moderate motivational practices, moderate level of teachers’ performance, weak relationship between motivational practices and the level of teachers’ performance in secondary schools in Kamwenge District. There is need for government and private sector to raise pay for the teachers; there is need for stakeholders in education to focus on increasing the employees’ motivation in factors such as the work itself, benefit programs, rewards, work conditions and prizes; promotions; allowances; staff training; school administrators should motivate employees to be more helpful, friendly and considerate to their co-workers and supervisors because this would increase the employees’ motivational level and enhance performance.